Evidence that dry eye represents a chronic overlapping pain condition. Issue 1 (September 2017) - Levitt, Alexandra E; Galor, Anat; Chowdhury, Aneesa R; Felix, Elizabeth R; Sarantopoulos, Constantine D; Zhuang, Gerald Y; Patin, Dennis; Maixner, William; Smith, Shad B; Martin, Eden R; Levitt, Roy C
Recent data suggest that corneal somatosensory dysfunction may be the underlying cause of severe dry eye symptoms in the absence of ocular surface pathology seen in a subset of patients diagnosed with "dry eye syndrome." This subset of patients tends to demonstrate a unique constellation of symptoms that are persistent, more severe, and generally respond poorly to current dry eye therapies targeting inadequate or dysfunctional tears. A growing body of literature suggests that symptoms in these patients may be better characterized as neuropathic ocular pain rather than dry eye. In these patients, dry eye symptoms are often associated with numerous comorbid pain conditions and evidence of central pain processing abnormalities, where eye pain is just one of multiple overlapping peripheral manifestations. In this review, we discuss the concept and potential mechanisms of chronic overlapping pain conditions as well as evidence for considering neuropathic ocular pain as one of these overlapping pain conditions.